Effect of head roll‐tilt on the subjective visual vertical in healthy participants: Towards better clinical measurement of gravity perception - Wada, Yoshiro (Laryngoscope Investig Otolaryngol, 2020)
OBJECTIVE: Gravity perception is an essential function for spatial orientation and postural stability; however, its assessment is not easy. We evaluated the head‐tilt perception gain (HTPG, that is, mean perceptual gain [perceived/actual tilt angle] during left or right head roll‐tilt conditions) and head‐upright subjective visual vertical (SVV) using a simple method developed by us to investigate the characteristics of gravity perception in healthy participants. METHODS: We measured the SVV and head roll‐tilt angle during head roll‐tilt within ±30° of vertical in the sitting and standing positions while the participant maintained an upright trunk (sitting, 434 participants; standing, 263 participants). We evaluated the head‐upright SVV, HTPG, and laterality of the HTPG. RESULTS: We determined the reference ranges of the absolute head‐upright SVV (<2.5°), HTPG (0.80‐1.25), and HTPG laterality (<10%) for the sitting position. The head‐upright SVV and HTPG laterality were not influenced by sex or age. However, the HTPG was significantly greater in women than in men and in middle‐aged (30‐64 years) and elderly (65‐88 years) participants than in young participants (18‐29 years). The HTPG, but not the head‐upright SVV or HTPG laterality, was significantly higher in the standing vs sitting position. CONCLUSION: The HTPG is a novel parameter of gravity perception involving functions of the peripheral otolith and neck somatosensory systems to the central nervous system. The HTPG in healthy participants is influenced by age and sex in the sitting position and immediately increases after standing to reinforce the righting reflex for unstable posture, which was not seen in the head‐upright SVV, previously considered the only parameter. LEVEL OF EVIDENCE: 4.